Concurrent Resistance to Carbapenem and Colistin Among Enterobacteriaceae Recovered From Human and Animal Sources in Nigeria Is Associated With Multiple Genetic Mechanisms - Ngbede, Emmanuel O.; Adekanmbi, Folasade; Poudel, Anil; Kalalah, Anwar; Kelly, Patrick; Yang, Yi; Adamu, Andrew M.; Daniel, Salem T.; Adikwu, Alex A.; Akwuobu, Chinedu A.; Abba, Paul O.; Mamfe, Levi M.; et al. (Frontiers in Microbiology, 2021)
Resistance to last resort drugs such as carbapenem and colistin is a serious health threat globally. In this study, we investigated carbapenem and colistin resistance in 583 non-duplicate Enterobacteriaceae isolates recovered from humans, animals and the environment in Nigeria using phenotypic methods and whole genome sequencing (WGS). Of the 583 isolates, 18.9% (110/583) were resistant to carbapenem while 9.1% (53/583) had concurrent carbapenem-colistin resistance. The minimum inhibitory concentrations of carbapenem and colistin were 2–32 µg/mL and 8-> 64 μg/mL, respectively. None of the carbapenem resistant isolates produced carbapenemase and none harboured any known carbapenemase producing genes. WGS revealed that concurrent carbapenem-colistin resistance was mediated by novel and previously described alterations in chromosomal efflux regulatory genes, particularly mgrB (M1V), ompC (M1_V24del), ompK37 (I70M, I128M), ramR (M1V) and marR (M1V). In addition, alterations/mutations were detected in the etpA, arnT, ccrB, pmrB in colistin resistant bacteria and ompK36 in carbapenem resistant bacteria. The bacterial isolates were distributed into 37 sequence types and characterized by the presence of internationally recognized high-risk clones, indicating humans and animals in Nigeria may serve as reservoirs and vehicles for the global spread of the isolates. Further studies on antimicrobial resistance in African countries is warranted.